THE INTEGRATION OF ISLAMIC LAW AND ISLAMIC ECONOMICS IN HALAL PRODUCT ASSURANCE: A HISTORICAL ANALYSIS OF ITS DEVELOPMENT IN OF HALAL ASSURANCE INDONESIA - Abdi Dzul Jalal Ikram; Siradjuddin; Rika Dwi Ayu Parmitasari (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study analyzes the development, characteristics, and significance of Islamic financial instruments within contemporary Islamic finance frameworks, particularly regarding their contributions to ethical financial practices and economic resilience. The purpose of this research is to identify how Islamic financial instruments operate conceptually and how they adapt to modern financial and technological developments. This research employed a qualitative approach through a library research method using scholarly publications, books, and official institutional documents as primary sources. The findings indicate that Islamic financial instruments do not simply replicate conventional products but represent an independent system grounded in Sharia principles, including risk sharing, asset-based transactions, and prohibition of speculative elements. The results also show that technological innovation, regulatory harmonization, and Sharia governance have become determining factors for sustainable development of Islamic financial instruments. Moreover, social financing mechanisms such as zakat, waqf, and charitable-based instruments expand financial inclusion and contribute to socio-economic empowerment. In conclusion, Islamic financial instruments hold substantial potential in establishing a more ethical, stable, and inclusive financial system. Further efforts are required to strengthen regulatory frameworks, institutional capacity, and digital transformation to enhance global integration and future implementation of Islamic finance.